A multi-institutional study of renal outcomes and renal-related pregnancy outcomes in uterus transplant recipients - Sawinski, Deirdre; Johannesson, Liza; Kristek, Jakub; Fronek, Jiri; O'Neill, Kathleen E; Gregg, Anthony; Testa, Giuliano; Porrett, Paige M (American journal of transplantation, 2022)
Uterus transplantation (UTx) is an effective treatment option for uterine factor infertility. However, the need for immunosuppression and congenital renal anomalies that coexist with uterine agenesis in about 30% of women with Mayer-Rokitansky-Kuster-Hauser syndrome create a risk for renal dysfunction. We therefore examined renal function trajectory and related pregnancy complications in an international cohort of 18 UTx recipients from September 2016-February 2020 who had at least one live birth. All UTx recipients had a diminution in their renal function that was apparent starting at 30 days posttransplant and in half the reduction in eGFR was at least 20%; the decrease in eGFR persisted into the early post-partum period. Half met criteria for Stage 1 acute kidney injury (AKI) as defined by the AKI Network criteria during their pregnancy. Overall, 28% of UTx recipients developed pre-eclampsia. eGFR was lower at embryo transfer and throughout pregnancy among those who developed pre-eclampsia, reaching statistical significance at week 16 of pregnancy. This effect was independent of tacrolimus levels. Mean eGFR remained significantly lower in the first 1-3 months after delivery. In the subgroup who reached 12 months of postpartum follow up and had a graft hysterectomy (n = 4), there was no longer a statistical difference in eGFR (pretransplant 106.7 ml/m ± 17.7 vs. 12 mos postpartum 92.6 ml/m ± 21.7, p = .13) but the number was small. Further study is required to delineate long term renal risks for UTx recipients, improve patient selection, and make decisions regarding a second pregnancy.
Keywords: Acute Kidney Injury; pre-eclampsia; kidney function; těhotenství; ženská infertilita; Uterus; výsledek těhotenství; uterus; Infertility, Female; ženské pohlaví; Humans; Pregnancy; příjemce transplantátu; Transplant Recipients; Pregnancy Outcome; ledviny; akutní poškození ledvin; uterus transplant; Kidney; Female; Pre-Eclampsia; preeklampsie; lidé